2013
DOI: 10.1002/hipo.22113
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of object recognition memory requires HRI kinase‐dependent phosphorylation of eIF2α in the hippocampus

Abstract: Local control of protein synthesis at synapses is crucial for synaptic plasticity and memory formation. However, little is known about the signals coupling neurotransmitter release with the translational machinery during these processes. Here, we studied the involvement of heme-regulated inhibitor (HRI) kinase, a kinase activated by nitric oxide that phosphorylates eukaryotic initiation factor 2α (eIF2α), in object recognition (OR) memory consolidation. Phosphorylated eIF2α mediates two opposing effects upon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 47 publications
2
23
0
1
Order By: Relevance
“…Conversely, the chemical increase of PKR dependent eIF2α phosphorylation in hippocampal neurons elevated ATF4 translation and suppressed CREB‐dependent gene expression, inhibiting LTP formation [Jiang et al, ]. The involvement of HRI was suggested using an object recognition model of memory, in which the authors observed a transient increase in the phosphorylation of eIF2α in dorsal CA1 that was dependent on HRI [ILL‐Raga et al, ].…”
Section: Eif2α In Memory Formation and Nervous System Developmentmentioning
confidence: 99%
“…Conversely, the chemical increase of PKR dependent eIF2α phosphorylation in hippocampal neurons elevated ATF4 translation and suppressed CREB‐dependent gene expression, inhibiting LTP formation [Jiang et al, ]. The involvement of HRI was suggested using an object recognition model of memory, in which the authors observed a transient increase in the phosphorylation of eIF2α in dorsal CA1 that was dependent on HRI [ILL‐Raga et al, ].…”
Section: Eif2α In Memory Formation and Nervous System Developmentmentioning
confidence: 99%
“…Des études de relations structure-activité ont permis d'améliorer les propriétés pharmacodynamiques de la molécule de départ. Par ailleurs, l'utilisation de ces nouveaux dérivés a permis l'étude du rôle de HRI dans la plasticité synaptique lors de tests d'apprentissage effectués chez le rat, suggérant que HRI peut être ciblée de façon pharmacologique [44]. Des études plus poussées devront cependant être réalisées afin de tester la spécificité de ces drogues et d'optimiser leurs propriétés thérapeutiques potentielles.…”
Section: Développement De Drogues Influençant L'expression De Hri Dévunclassified
“…Several studies in mice have also been interpreted to indicate that ATF4 impairs LTP and memory consolidation (Chen et al, 2003; Costa-Mattioli et al, 2005, 2007; Jiang et al, 2010). On the other hand, additional reports suggest that ATF4 is required for behavioral flexibility (Trinh et al, 2012) and consolidation of object recognition memory (Ill-Raga et al, 2013) and enhances memory for fear extinction (Wei et al, 2012). The apparently diverging views of ATF4's role in learning and memory may reflect the use of indirect and likely non-selective means that have been used to experimentally affect ATF4 expression.…”
Section: Introductionmentioning
confidence: 99%